Genetic diversity in Cymbopogon khasianus (Hack.) Stapf ex Bor collected from Meghalaya, Northeast India, using PCR-based dominant markers - Dutta, Sukriti; Munda, Sunita; Baruah, Joyashree; Lal, Mohan (Current Botany, 2025)
Cymbopogon is a globally recognized genus of medicinal, aromatic, and economically important grasses within the monocots, cultivated primarily for its high-value essential oil. The essential oil extracted from this crop has significant commercial and pharmaceutical applications. In the present study, a total of 48 germplasm lines of Cymbopogon khasianus (Hack.) Stapf ex Bor were collected from the Meghalaya region of Northeast India. Although these germplasms belong to the same species and chemotype, considerable morphological variation was observed among them. Therefore, 41 DNA-based dominant molecular markers, including 21 RAPD and 20 ISSR primers, were employed to assess and confirm the genetic diversity of the germplasm. Dendrograms generated through UPGMA and cluster analysis based on ISSR, RAPD, and combined datasets were largely similar and effectively separated the genotypes into distinct clusters. ISSR markers demonstrated higher efficiency, showing greater average PIC, MI, and Rp values (0.129, 2.28, and 2.13, respectively) compared to RAPD markers (0.097, 0.95, and 1.15). Additionally, ISSR primers exhibited a higher percentage of polymorphic bands (91.50%) than RAPD primers (81.59%). AMOVA results further supported the superiority of ISSR markers over RAPD markers. Overall, the findings of this study will contribute to the conservation and improvement of C. khasianus germplasm.